2009
DOI: 10.1091/mbc.e08-07-0754
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Orc6 Facilitates GTPase Activity and Filament Formation of the Septin Complex

Abstract: The origin recognition complex or ORC is a six-subunit protein important for DNA replication and other cell functions. Orc6, the smallest subunit of ORC, is essential for both replication and cytokinesis in Drosophila, and interacts with the septin protein Pnut, which is part of the Drosophila septin complex. In this study, we describe the analysis of the interaction of Orc6 with Pnut and whole Drosophila septin complex. Septin complex was purified from Drosophila embryos and also reconstituted from recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 48 publications
9
76
1
3
Order By: Relevance
“…The fact that inactivation of the Orc6 NLS prevents both nuclear localization of Orc6 and cell proliferation demonstrates that nuclear localization of Orc6 is essential to Orc6 function. In the absence of Orc6 function, cells accumulated both in G 1 and in G 2 or M phase, consistent with previous reports that siRNA suppression of either human or Drosophila Orc6 expression retards both DNA replication and cytokinesis (27,28).…”
Section: Nuclear Localization Of Orc6-humansupporting
confidence: 92%
“…The fact that inactivation of the Orc6 NLS prevents both nuclear localization of Orc6 and cell proliferation demonstrates that nuclear localization of Orc6 is essential to Orc6 function. In the absence of Orc6 function, cells accumulated both in G 1 and in G 2 or M phase, consistent with previous reports that siRNA suppression of either human or Drosophila Orc6 expression retards both DNA replication and cytokinesis (27,28).…”
Section: Nuclear Localization Of Orc6-humansupporting
confidence: 92%
“…The larger, N-terminal domain is important for replication, whereas the smaller, C-terminal domain is required for the interaction with Pnut protein and cytokinesis function of Orc6, as demonstrated by our earlier in vitro and cell culture-based studies (18,23). To learn more about the functions of the C-terminal domain in vivo, we designed GFP-Orc6 transgenes containing C-terminal deletions or point mutations and used them in rescue experiments.…”
Section: Generation Of An Orc6 Mutation In Drosophilamentioning
confidence: 99%
“…This apparent inconsistency may reflect the difference in affinity of Orc6 for the core ORC1-5 complex in distant metazoan species. Drosophila Orc6 and human Orc6 also have a function in cytokinesis (7,22,23). This function in Drosophila is attributed to the C-terminal domain of Orc6 (22).…”
mentioning
confidence: 99%
“…The conservative N-terminal domain is responsible for DNA interaction, and in metazoans shows structural homology with the transcription factor TFIIB [100]. A small variable domain at the C-terminus is responsible for interactions with other proteins, and with ORC3, in particular [20,101,102]. Besides that, it was demonstrated that the C-terminal domain contains a motif which mediates an ORC6 interaction with the Pnut protein, a component of the septin complex [20].…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%
“…Besides that, it was demonstrated that the C-terminal domain contains a motif which mediates an ORC6 interaction with the Pnut protein, a component of the septin complex [20]. ORC6 promotes septin polymerization due to its ability to form a dimer [102,103]. Although the molecular mechanism for the septin filament assembly still remains poorly understood, the results obtained so far provide strong evidence for the direct involvement of ORC6 in this process.…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%